Dealing about wheeling in Augustan Thebes. A Demotic lease of a cart (O.Ashm.Dem. 28) - Winkler, A (Harrasowitz Verlag, 2018)
Demotic Ostracon Ashmolean Museum no. 28 (hereafter: O.Ashm.Dem. 28) is an early Roman-period pottery sherd from the Thebaid. It records a lease of a transport cart for hauling a harvest. Similar pieces are rare. There are only a few Demotic texts that concern the conveyance of mobile property in any form, not including animals or bridal gifts. The Greek and Coptic documentation relating to similar transactions is also sporadic. To this date, there are only two published texts, which are comparable to O.Ashm.Dem. 28, that is, well-preserved deeds providing a detailed description of a vehicle as well as regulations for the transaction. Both these documents stem from Aphrodito but are not related to each other directly. The first papyrus is a Greek LateAntique lease of a transport cart from the famous Dioskoros Archive (P.Cair.Masp. III 67303) dating to the 6th cent. AD. The second one is a Coptic sale of a threshing cart (P.Copt.Vat.Dor. 1) from the 7th cent. AD.